2016
DOI: 10.1016/j.compbiomed.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution analysis over graphs for a motor imagery based online BCI game

Abstract: Multiresolution analysis (MRA) over graph representation of EEG data has proved to be a promising method for offline brain-computer interfacing (BCI) data analysis. For the first time we aim to prove the feasibility of the graph lifting transform in an online BCI system. Instead of developing a pointer device or a wheel-chair controller as test bed for human-machine interaction, we have designed and developed an engaging game which can be controlled by means of imaginary limb movements. Some modifications to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 21 publications
0
16
0
2
Order By: Relevance
“…Thus, it is extremely useful to investigate new methodologies that can offer a better understanding of how motor imagined patterns and connectivity differs from the non-imagined/realized activities. Recently, new research has investigated the possibility of taking measures that were originally developed in graph theory for data classification as they could provide important information about the connectivity [80]. In particular, a recent study has shown that graph metrics can be used for EEG-BCIs based on hand motor imagery graphs, as they are a feasible option for classification of hand motor imagined signals [81].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thus, it is extremely useful to investigate new methodologies that can offer a better understanding of how motor imagined patterns and connectivity differs from the non-imagined/realized activities. Recently, new research has investigated the possibility of taking measures that were originally developed in graph theory for data classification as they could provide important information about the connectivity [80]. In particular, a recent study has shown that graph metrics can be used for EEG-BCIs based on hand motor imagery graphs, as they are a feasible option for classification of hand motor imagined signals [81].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Thus, [21] applied the common spatial pattern method, [22] implicated modified regression algorithm, [4] used coefficient of determination for the evaluation of spectral features topographies. The mapping method realized in this work allowed obtaining decoding accuracies for each channel that makes the selection of informative channels numerically validated but requires computational resources.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, wavelet analysis has been widely used in EEG-based MI applications due to its ability to offer temporal-spectral analysis across different resolution levels [ 7 ]. Most recently, there have been a few attempts to use graph metrics as features for MI classification algorithms [ 8 ]. The main difference in this research with respect to the above-mentioned analysis lies in the fact that the classification process is made using graph theory features extracted from the synchrostates, a novel concept never used before for classification of MI tasks.…”
Section: Introductionmentioning
confidence: 99%